Etnografi som teori, metod och livsstil - Thomas Johansson (Educare)
Ethnography is used and applied as a scientific method and methodology in various disciplines and scientific areas. This method has its roots in social anthropology, sociology and ethnology. Today there is an increasing and renewed interest in ethnography. In this article I try to combine a more general discussion on ethnography as a method and methodology, with a discussion on the use of this method within educational science and pedagogy. The main parts of the ethnographic studies conducted within Swedish and international educational research are located to a restricted institutional and organisational setting and place, namely the school. The main focus is thereby on children’s and young people’s movements, behaviour and interactions within this specific setting. However, there is a lack of studies of young people’s movements in space and time, and of the relation between academic training and leisure time activities. There is also a lack of studies on the relation between the school and the surrounding world. To find these kinds of empirical studies we have to move outside educational research and look into, for example, sociology and youth culture research. In this article the possibility of connecting and relating different types of ethnographic research and fields of research is explored and analysed. This discussion is also elaborated into a more general discussion on the use of theory in ethnographic research.